Cultural proximity and reflexivity in interpreting transnational media texts: the case of Malaysians consuming Japanese popular culture - Yamato, Eriko (Nova Southeastern University, 2014)
Television programs such as animation and drama series from Japan have be come common transnational products in Malaysia. Since studies on Malaysians who consume Japanese popular culture are lacking even a decade after its substantial rise in popularity, this qualitative study was designed to explore the media consumption of Japanese popular culture in Malaysia. In this article I examined how Malaysians are interpreting their favorite media texts from Japan specifically revisiting the concepts of “cultural proximity” and “reflexivity” suggested in the other studies of Japanese popular culture and the audience. I conducted in-depth interviews with 12 participants who have been consuming various Japanese popular cultural products over the years, and thematically analyzed transcribed audio-recordings of the interviews. Individual proximity in the particular life stage was found in their favorite media texts, and that was a part of their pleasure in addition to enjoying encountering foreignness, which they did not find or accept in their real lives. Transnational media texts of Japanese popular culture are suggested to be potential materials to reflect upon and discuss the individual proximity in people, social issues, or phenomenon rather than essential “culture” which is often associated with national or ethnic origin.